Analisis Tingkat Motivasi Belajar Siswa Overweight pada Pembelajaran Pendidikan Jasmani - Gabriella Jessica Pongbura; Faridha Nurhayati (Smart Education, 2024)
Abstract: Physical education studies how to use physical activity to improve and create positive outcomes for physical, mental, and emotional health. Of course, students must be motivated to set appropriate learning objectives for their physical education lessons. Being overweight hurts student motivation. This study aims to determine the motivational difference between overweight and normal-weight students in SMA Hang Tuah 2 Sidoarjo physical education classes. The research method used was descriptive, with a quantitative approach. This study's population consisted of 179 students from class XI, and the sampling technique used was purposive sampling. The research instrument included standard anthropometric calculations, a body mass index based on age, and a learning motivation questionnaire. The t-test is used to analyze the data. According to the data analysis results, there is no difference in physical education learning between overweight students and students of average weight at Hangtuah 2 Sidoarjo High School (p-value = 0.845 > 0.05). Because the average learning motivation between students in the overweight and normal categories is in the